Characterization of gene encoded for dioxygenase in dibenzofuran degrading Terrabacter sp. strain DMA isolated from herbicide/dioxin contaminated soil in Da Nang - Huu, Nguyen Ba; Cam Ha, Dang Thi (Academia Journal of Biology, 2014)
The dibenzofuran degrading bacterium DMA strain was isolated from heavy herbicide/dioxin contaminated soil in a US former military base at Danang airport. Colony of DMA is lemon yellow, round, slight convex and 1.5 - 2 mm diameter after 7 days of incubation in mineral medium containing dibenzofuran. Cells were Gram-positive, cocci shaped, with diameter ranging from 0.27 - 0.53 mm. 16S rDNA sequence analysis indicated that strain DMA was closely related to Janibacter limous DSM 11140T (97.3%), Terrabacter sp. YK7 (97.5%) and Terrabacter sp. YK3 (96.7%). Based on morphological characteristics and analysis of 16S rARN gene sequence, DMA strain should be placed in genus Terrabacter and named Terrabacter sp. DMA. The primer pair DIOXY-F vµ DIOXY-R were designed based on comparison of many genes encoded for alfa subunit dioxygenase from aromatic hydrocarbon, dibenzofuran and dioxin degrading bacteria. The PCR product amplified from total DNA of DMA strain was showed high similar levels 97% to dbfA1 genes in Rhodococcus sp. DFA3, Terrabacter sp. DBF63 and Rhodococcus sp. YK2; 96% to gene encoded alpha putative terminal dioxygenaza in Mycobacterium sp. YK18. All of these Gram-positive bacterial strains are able to degrade dibenzofuran.